Curve of Spee modification in different vertical skeletal patterns after clear aligner therapy: a 3D set-up retrospective study - Domenico Ciavarella; Carlotta Fanelli; Carmela Suriano; Alessandra Campobasso; Mauro Lorusso; Donatella Ferrara; Marta Maci; Rosa Esposito; Michele Tepedino (SpringerOpen, 2024)
Abstract Objective The purpose of the present study was to evaluate: (1) changes in the curve of Spee (COS) after clear aligner therapy and (2) whether such changes correlated with the patient's skeletal patterns. Materials and methods Three-dimensional mandibular models of 106 patients (47 males and 59 females; mean age 22.3 SD ± 3.4 years) treated with clear aligners were retrospectively analysed. The perpendicular distance between the occlusal reference plane and the buccal cusp tip of each lateral tooth was measured. Five angular cephalometric measurements (PP-MP, PP-OP, OP-MP, AFH, and PFH) were performed and correlated with the T1-T0 difference in linear distances. The patients were divided into three groups according to facial divergence. Variance analysis with Tukey post hoc correction was performed to evaluate the differences among groups. Results The one-way ANOVA test showed a statistically significant difference for all analysed variables, except for the change in the distance of the second molar from the occlusal reference plane. Tukey's HSD test showed the following differences: In normodivergents, the T1-T0 difference in the distance of the first molar from the occlusal plane was 1 mm greater than that observed in the hyperdivergent group (p < 0.05); in the normodivergent group, the T1-T0 difference in the distance of the second premolar from the occlusal plane was 1.23 mm greater than that observed in the hyperdivergent group (p < 0.05), while in the hypodivergent group, it was 1.08 mm greater than in the hyperdivergent group (p < 0.05); finally, in normodivergents, the T1-T0 difference in the distance of the first premolar from the occlusal plane was 0.97 mm greater than that observed in the hyperdivergent group (p < 0.05). Conclusion Treatment with aligners did not lead to a clinically significant change in COS depth. However, when dividing the sample into groups based on craniofacial divergence, COS depth change differed significantly between the three groups.